PARIWISATA DESA BERKELANJUTAN: STUD I KASUS DESA WISATA JATILUWIH, BALI - Sri Puspaadi, Ida Ayu (JURNAL KEPARIWISATAAN, 2011)
The village of Jatiluwih was developed as one of sustainable village tourism in Bali in I 990s. The development was based upon sustainable tourism developÂment principles by using the Balinese concepts of harmony called 'Tri Hita Karan a' or the three causes of happiness which comprise: harmonious relationship between people with God, people with other people and people with the environÂment. This research aimed to investigate the impacts of the village tourism development on economic, social-cultural and environmental aspects. The study was conducted qualitatively and the data were collected using non participatory interviews with key informants comprising of village community leaders, some people involved in the initial project as well as the people currently involved in organizing some aspects of the village tourism. Interview were also conducted to formal leaders. The result of the study showed that village tourism development had positive impacts on the three aspects, however, few villagers obtained direct economic benefits. Despite its limited direct economic benefits, the villagers supported the development and had positive attitude toward tourism development in their village.